2006
DOI: 10.1136/hrt.2004.057497
|View full text |Cite
|
Sign up to set email alerts
|

Long term cardiac follow up of severe twin to twin transfusion syndrome after intrauterine laser coagulation

Abstract: Objective: To assess long term changes in cardiac morphology and function in survivors of severe twin to twin transfusion syndrome (TTTS) after intrauterine laser coagulation of placental anastomoses. Design: Prospective follow up of fetuses with severe TTTS treated by laser coagulation of intrauterine placental anastomoses. Fetal echocardiography and Doppler studies of feto-placental haemodynamic function were performed at the time of laser coagulation (median gestational age of 21.7 weeks). Postnatal cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
96
3
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 35 publications
13
96
3
1
Order By: Relevance
“…TTTS has been associated with polyhydramnios and myocardial changes, including acquired right ventricular outflow tract obstruction, which occurs in ≈10% of recipient twin fetuses. 84 Atrial septal defects have also been reported postnatally in either twin. 84,133 The incidence of pulmonary stenosis may be lower if the pregnancy is successfully treated with invasive laser photocoagulation of the intertwin anastomosis.…”
Section: Monochorionic Twinningmentioning
confidence: 99%
See 2 more Smart Citations
“…TTTS has been associated with polyhydramnios and myocardial changes, including acquired right ventricular outflow tract obstruction, which occurs in ≈10% of recipient twin fetuses. 84 Atrial septal defects have also been reported postnatally in either twin. 84,133 The incidence of pulmonary stenosis may be lower if the pregnancy is successfully treated with invasive laser photocoagulation of the intertwin anastomosis.…”
Section: Monochorionic Twinningmentioning
confidence: 99%
“…84,133 The incidence of pulmonary stenosis may be lower if the pregnancy is successfully treated with invasive laser photocoagulation of the intertwin anastomosis. 84,133,134 Fetal echocardiogram is recommended in all monochorionic twin gestations.…”
Section: Monochorionic Twinningmentioning
confidence: 99%
See 1 more Smart Citation
“…8,[29][30][31] However, an increased congenital heart defect risk was also found in the non-TTTS monochorionic twins. Overall, VSDs were found to be the most frequent in this sample of monochorionic/diamniotic twin gestations, whereas pulmonary stenosis and atrial septal defects were significantly more prevalent in pregnancies complicated by TTTS.…”
Section: Inpatientsmentioning
confidence: 96%
“…137 Eighty seven percent recipient twins who survived after laser treatment for severe TTTS, were reported to have normal cardiac function at about 2 years after delivery. 138 Other complications that have been documented with laser treatment involve amniotic fluid leakage into the maternal peritoneal cavity, vaginal bleeding, placental abruption and chorioamnionitis. 64,79 The instruments used for laser photocoagulation are of larger diameter than the spinal needle that are usually preferred for amnioreduction or even septostomy and even that factor is enough to increase the risk of complications.…”
Section: Complications Of Laser Treatmentmentioning
confidence: 99%